Morbidity and mortality among older people admitted to nursing home. (25th November 2019) - Reilev, Mette; Lundby, Carina; Jensen, John; Larsen, Søren Post; Hoffmann, Helene; Pottegård, Anton
Abstract: Background: the increasing number of multimorbid older people places high demands on future health care systems. To inform the discussion on how to structure future care strategies, we aimed to describe the temporal relationship between admission, and morbidity and mortality in nursing home residents. Methods: data on 5, 179 older individuals admitted to 94 Danish nursing homes in 12 municipalities during 2015–2017 were linked to the nationwide Danish health registries to retrieve information on the temporal relation between nursing home admission and morbidity and mortality. Results: at the time of nursing home admission, the majority were women (63%). Male residents were younger than women (median 82 vs 85 years) and had a higher prevalence of comorbidities (median Charlson score 2 vs 1 among women). The median survival after nursing home admission was 25.8 months, with the 3-year survival being 37%. Three-year survival was lower among men (29 vs 43% among women) and among the oldest residents (23% among those aged ≥90 years vs 64% among individuals ≤65 years). In addition to age and sex, predictors of mortality included hospitalisations prior to nursing home admission and a high burden of comorbidity. The rate of hospitalisations, primarily for reasons related to frailty, increased substantially during the 9 months prior to nursing home admission. Conclusion: we provide detailed information on differences in morbidity and mortality across age span and sex at the time of nursing home admission, thereby contributing to the ongoing discussion of how to structure the future health care system.